2011
DOI: 10.1111/j.1399-0004.2011.01765.x
|View full text |Cite
|
Sign up to set email alerts
|

Facial asymmetry and clinical manifestations in patients with novel insertion of theTCOF1gene

Abstract: This study explored the role of TCOF1 insertion mutations in Taiwanese patients with craniofacial anomalies. Twelve patients with single or multiple, asymmetrical congenital craniofacial anomalies were enrolled. Genomic DNA was prepared from leukocytes; the coding regions of TCOF1 were analyzed by polymerase chain reaction and direct sequencing. Clinical manifestations were correlated to the TCOF1 mutation. Six of 12 patients diagnosed with hemifacial microsomia exhibited a novel insertion mutation 4127 ins G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…From a cohort of 169 patients, Estelle Lopez et al found MYT1 mutation in a sporadic case by whole exon sequencing and detected one heterozygous missense mutation in another patient (Lopez et al, 2016). Other genes related to HM included SALL1, BAPX1, TCOF1, and EFTUD2 (Fischer et al, 2006;Kosaki et al, 2007;Su et al, 2012;Dai et al, 2016;Rengasamy Venugopalan et al, 2017). Here, we present the genetic studies of a family with autosomal dominant HM and demonstrate the role of the EDN-PLC-DLX5/6 regulatory cascade in HM.…”
Section: Introductionmentioning
confidence: 56%
“…From a cohort of 169 patients, Estelle Lopez et al found MYT1 mutation in a sporadic case by whole exon sequencing and detected one heterozygous missense mutation in another patient (Lopez et al, 2016). Other genes related to HM included SALL1, BAPX1, TCOF1, and EFTUD2 (Fischer et al, 2006;Kosaki et al, 2007;Su et al, 2012;Dai et al, 2016;Rengasamy Venugopalan et al, 2017). Here, we present the genetic studies of a family with autosomal dominant HM and demonstrate the role of the EDN-PLC-DLX5/6 regulatory cascade in HM.…”
Section: Introductionmentioning
confidence: 56%
“…At the molecular level, a number of genes and factors have been associated with asymmetric growth, identified in models of severe asymmetry associated with such syndromes as hemifacial microsomia, craniosynostosis and craniofacial clefts [19]. While genes, like Msx1, Goosecoid, TWIST, and TCOF1 have been linked to a number of craniofacial syndromes, no single gene has been identified as the sole cause of the skeletal abnormalities [20-23]. It is possible that a number of genes found within similar chromosomal loci are involved in these syndromes due to compromise during the embryonic period.…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetry of bite force was found only in dolichofacial subjects, with a higher bite force exerted on the left side []. Moreover, the role of TCOF1 insertion mutations in Taiwanese patients with craniofacial anomalies was studied; the mutant treacle probably exhibited defects in nuclear trafficking and appeared to affect the development of the left side of the face (6/6 cases) more than the right side of the face (0/6) []. Although these results may be related to our findings, the reason why facial asymmetry and internal derangement are observed more frequently on the left side than on the right side could not be elucidated.…”
Section: Discussionmentioning
confidence: 65%